“Estudio técnico para elaboración de ahumado de pescado a partir de especies amazónicas “PACO (piaractus brachypomus) Y Gamitana ( Colossoma macropomum)” - Pinedo Carranza, Ramiro (2000)
The Paco (Piaractus brachypomus) and the Gamitana (Colossoma macropomus) are species of greater consumption by them settlers of the Amazon Peruvian, their meats are very listed and have good features. Optimal for both processing flow fish was: raw material, heavy/wash, desescamado and gutted, washed, filleting, Bled, drained, salted, wash/desalted, seasoned, aired, smoked, cooled, packaged and stored. Using these species were processes of smoked memdiante hot smoking technique, where the parameters of this process were: T ° = 35 to 84° C, 0 = 4 hours in Paco and T ° = 35 to 84° C, e = 5 hours on to the Gamitana. Tests are developed characterizing the raw and trials in the various operations of the process. The salty was in battery wet to a concentration of 30% of salt (NaCl), to a time of 6 to 8 hours, being the time of 6 hours the more suitable for the fish Paco and 8 hours for the Gamitana. We then proceeded to u...